Per una totalità “nascosta”. Fortini, il presente, la figura - Fichera, Gabriele (L'ospite ingrato, 2021)
This essay, starting from the reconstruction of the theoretical dialogue that Fortini established with the “Pascalian” Goldmann of Deus absconditus as early as the 1950s, aims to show which complex ideological and political articulations the Fortinian concept of the “present” as a hidden totality is tinged with. This “present” appears to us in all its paradoxical problematic nature, as a dialectical and figural unity of past-present-future. The contribution analyzes and reconstructs a series of Fortinian passages that are placed in this path, between poetic texts belonging to different collections – Questo muro (1973), Paesaggio con serpente (1984), up to Composita solvantur (1994) – and essays, both literary and political, in a wide chronological span. It is also shown how, following the traces of this present absconditus, Fortini crosses his essential phares in a decidedly meaningful way: the ethically restless Manzoni of Providence / Foresight and the dreamlike and figural Dante of Purgatory.